2019
DOI: 10.1177/0898264319870400
|View full text |Cite
|
Sign up to set email alerts
|

Driving Cessation and Social Isolation in Older Adults

Abstract: Objective: This study investigated the impact of driving cessation on social isolation in older adults. Method: Data were obtained from Rounds 1 through 6 of the National Health and Aging Trends Study. The study sample consisted of 6,916 Medicare beneficiaries aged 65 or above who were eligible drivers at baseline. Mixed-effects ordered logistic regression and piecewise regression were used to examine the impact of driving cessation on social isolation. Results: In multivariable mixed-effects ordered logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…Although not directly testable with our data, this finding may suggest that functional impairment (i.e., no longer being able to drive) helps explain why health problems are associated with suicide (55). While driving cessation is more common among women than men (56)(57)(58)(59), studies suggest that driving cessation fractures social connections for men more than for women (31,60). Further, aging adults belonging to minority racial groups have also been found to be more likely to stop driving, although their risk of suicide is much lower than that of non-Hispanic whites (56,57).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although not directly testable with our data, this finding may suggest that functional impairment (i.e., no longer being able to drive) helps explain why health problems are associated with suicide (55). While driving cessation is more common among women than men (56)(57)(58)(59), studies suggest that driving cessation fractures social connections for men more than for women (31,60). Further, aging adults belonging to minority racial groups have also been found to be more likely to stop driving, although their risk of suicide is much lower than that of non-Hispanic whites (56,57).…”
Section: Discussionmentioning
confidence: 57%
“…Although the relationship between driving cessation and depression is well-documented, to our knowledge, the frequency of suicide related to driving cessation among aging adults has never been estimated (30)(31)(32). Therefore, the present analysis aims to (1) Estimate the frequency of driving cessation associated suicide among aging adults, (2) describe the salient circumstances and features of decedents of suicide associated with driving cessation using quantitative and qualitative approaches, and (3) discuss the utility of a supervised random forest algorithm in identifying driving cessation associated suicides.…”
Section: Introductionmentioning
confidence: 99%
“…Control variables in our models were also limited because we considered comparability between the two surveys. For instance, although several studies suggested transport difficulties including driving cessation, or geographic location as possible risk factors for social isolation among older adults, we could not include these factors 30 . Third, JAGES data are not representative of the whole country.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also found that mobility loss in late-life causes depression and feelings of social isolation (e.g. Fonda et al 2001;Qin et al 2019).…”
Section: Transport Mobility and Well-being In Late-lifementioning
confidence: 99%